PENERAPAN KARAKTER KEDISIPLINAN DI MI NIHAYATUL AMAL GUNUNGSARI KABUPATEN CIREBON - Widia Nur Jannah; Aiman Faiz; Qonita Pradina (PROCEEDING UMSURABAYA, 2022)
Character learning is a planned effort to improve a good personality. The purpose of this study is to reveal the concept of discipline applied at MI Nihayatul Amal Gunungsari, Cirebon Regency as a reference for other research that has a similar research concept. The research method used is descriptive analysis using interviews and observations to obtain research data. The results of the study reveal that in the implementation of character education with disciplined values, the teacher has carried out his role as an exemplary educator in setting an example that can be applied by students. Discipline in the teacher is very important to shape the character of good students, such as coming to school on time, using good and polite speech, and wearing neat, clean and polite clothes, so that students have followed the discipline that the teacher applies by example. The teacher also acts as a motivator to provide rewards and punishments as a motivation for students to generate a sense of responsibility towards discipline and as an appreciation in shaping the character of students' discipline at school. Thus, the important role of teachers as modeling in schools is one of the important factors in instilling the value of discipline for students at MI Nihayatul Amal Gunungsari, Cirebon Regency.Â Keywords: Character education; exemplary teacher; discipline